Feasibility of Dose Escalation in Patients With Intracranial Pediatric Ependymoma - Tensaouti, Fatima; Ducassou, Anne; Chaltiel, Léonor; Bolle, Stéphanie; Habrand, Jean Louis; Alapetite, Claire; Coche-Dequeant, Bernard; Bernier, Valérie; Claude, Line; Carrie, Christian; Padovani, Laetitia; Muracciole, Xavier; et al. (Frontiers in Oncology, 2019)
Background and purpose Pediatric ependymoma carries a dismal prognosis, mainly owing to local relapse within RT fields. The current prospective European approach is to increase the radiation dose with a sequential hypofractionated stereotactic boost. In this study, we assessed the possibility of using a simultaneous integrated boost (SIB), comparing VMAT versus IMPT dose delivery. Material and methods The cohort included 101 patients. The dose to planning target volume (PTV59.4) was 59.4/1.8 Gy, and the dose to SIB volume (PTV67.6) was 67.6/2.05 Gy. Gross tumor volume (GTV) was defined as the tumor bed plus residual tumor, clinical target volume (CTV59.4) was GTV + 5 mm, and PTV59.4 was CTV59.4 + 3 mm. PTV67.6 was GTV+ 3 mm. After treatment plan optimization, quality indices and doses to target volume and organs at risk (OARs) were extracted and compared with the standard radiation doses that were actually delivered (median = 59.4 Gy [50.4 59.4]). Results In most cases, the proton treatment resulted in higher quality indices (p < 0.001). Compared with the doses that were initially delivered, mean and maximum doses to some OARs were no higher with SIB VMAT, and significantly lower with protons (p < 0.001). In the case of posterior fossa tumor, there was a lower dose to the brainstem with protons, in terms of V59 Gy, mean and near-maximum (D2%) doses. Conclusion Dose escalation with intensity-modulated proton or photon SIB is feasible in some patients. This approach could be considered for children with unresectable residue or postoperative FLAIR abnormalities, particularly if they have supratentorial tumors. It should not be considered for infratentorial tumors encasing the brainstem or extending to the medulla.